Strategi Bertahan Pengemudi Ojol di Masa Pandemi Covid-19 di Kota Makassar - Nur Damayanti (Emik, 2021)
The online motorcycle taxi application (ojol) has become one of the most widely used applications by the people of Indonesia. However, since the outbreak of Covid-19 in Indonesia, including Makassar, something has been "missing" from the applications, such as Gojek and Grab. At Gojek there is no longer a motorbike ordering menu (Goride); while in Grab, the GrabBike menu also disappeared. The menu disappeared as a result of government policies through the implementation of Large-Scale Social Restrictions (PSBB) in order to break the chain of the spread of Covid-19. In order to continue to work in the midst of the Covid-19 pandemic, ojol drivers use various strategies. This article focuses on how the strategy of ojol drivers to survive during the Covid-19 pandemic. Using qualitative approach, this study was carried out in Makassar as a metropolitan city, as one of the cities where ojol transportation drivers operate, as well as the city with the highest number of Covid-19 cases. There are fifteen informants who participated in this study, consisting of eight Gojek drivers and the rest were Grab drivers. Data was collected using the combination of observation and in-depth interview techniques. The study shows that the income of ojol drivers has decreased drastically since the Covid-19 outbreak, as the consequence of government policies through the PSBB which limited people’s mobility, including ojol drivers. In order to survive, ojol drivers use various strategies, such as living in a state of frugality, taking additional work (such as selling food in offline system, being a construction worker, opening a small tavern, etc.). When conditions gradually improve and the PSBB policy is relaxed, they can again work with the application of general health protocols (3M: wearing masks, washing hands, and maintaining distance) and the application of specific health protocols is also enforced (such as the use of plastic insulators for taxi drivers or passengers carrying their own helmets for motorcycle taxis), so that they can continue to work to make a living in the middle of pandemic Covid-19, even though the income is not yet fully recovered.